Corrigendum to ’Visible light photocatalytic enhanced heterogeneous cobalt catalyzed peroxymonosulfate synergistic process to degradation atrazine: Efficiency, influencing factors, by-products removal and mechanism’[Volume 159, January 2026, Pages 166-177] - Qingkong Chen; Jieyu Xia; Fengjun Liu; Jianping Fan; Peng Yan; Mika Sillanpää (Journal of Environmental Sciences, 2026)

Inhibition of postharvest soft rot in Chinese flowering cabbage by propyl gallate - Fengjun Li; Zhili Xu; Longlong Song; Lilang Li; Hai Liu; Yan Liao; Yuntao Zhao (Postharvest Biology and Technology, 2026)

Visible light photocatalytic enhanced heterogeneous cobalt catalyzed peroxymonosulfate synergistic process to degradation atrazine: Efficiency, influencing factors, by-products removal and mechanism - Qingkong Chen; Jieyu Xia; Fengjun Liu; Jianping Fan; Peng Yan; Mika Sillanpää (Journal of Environmental Sciences, 2026)

Physiological and transcriptomic insights into low temperature-induced suppression of internal browning in postharvest pineapple (Ananas comosus L.) - Longlong Song; Zhili Xu; Fengjun Li; Hai Liu; Lilang Li; Yan Liao; Yuntao Zhao (Postharvest Biology and Technology, 2025)

Effects of fermentation on the quality, flavor, and bacterial community changes of Longtian Zharou-a traditional Chinese fermented meat product - Aihua Lou; Xiping Jin; Zhuoqi Dong; Yaodong Wei; Yanyang Wu; Fengjun Xiao; Wei Quan; Yan Liu; Qingwu Shen; Jie Luo; Lei Zhou (Innovative Food Science & Emerging Technologies, 2025)

Sedimentary Environment, Tectonic Setting, and Uranium Mineralization Implications of the Yimin Formation, Kelulun Depression, Hailar Basin, China - Fanmin Meng; Fengjun Nie; Fei Xia; Zhaobin Yan; Da Sun; Wenbo Zhou; Xin Zhang; Qing Wang (Journal of Marine Science and Engineering, 2024)
The sandstone-type uranium deposit of the Kelulun Depression is the first industrially valuable uranium deposit discovered in the Hailar Basin. This study performed a systematic examination of 17 sandstone samples from the Yimin Formation in the Kelulun Depression based on various analytical techniques. The findings of the current study were synthesized with previous research to investigate the impact of the redox conditions and the tectonic background of the source area, as well as the paleoclimatic evolution of the Yimin Formation on uranium mineralization. The elemental Mo, U/Th, V/Cr, Ni/Co, and V/(V + Ni) ratios indicate that the paleowater was in an oxygen-rich environment during the deposition of the Yimin Formation. Additionally, the C-value, Sr/Cu, Al2O3/MgO, and Rb/Sr ratios indicate that the Yimin Formation was formed in a paleoclimate characterized by arid-to-semi-arid conditions. The geochemical characteristics of the observed elements indicated that the sediment source of the Yimin Formation was mainly felsic rocks from the upper continental crust, the weathering of the rock was weak, and the tectonic background was a passive continental margin. Coffinite is distributed in the form of cementation and stellates within or around pyrite crystals, and uranium-titanium oxide is mostly distributed in an irregular granular distribution in the biotite cleavage fractures of the study area. In summary, the findings of this study reveal that the tectonic settings, provenance, uranium source, paleoclimate, and oxygen-rich paleowater of the Yimin Formation have important geological significance for the large-scale uranium mineralization of the Kelulun Depression.

Newcastle disease virus suppresses antigen presentation via inhibiting IL-12 expression in dendritic cells - Fulong Nan; Wenlong Nan; Xin Yan; Hui Wang; Shasha Jiang; Shuyun Zhang; Zhongjie Yu; Xianjuan Zhang; Fengjun Liu; Jun Li; Xiaoqiong Zhou; Delei Niu; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Microbial regulation of aggregate stability and carbon sequestration under long-term conservation tillage and nitrogen application - Mengni Zhang; Xiaojun Song; Xueping Wu; Fengjun Zheng; Shengping Li; Yan Zhuang; Xvlun Man; Aurore Degré (Sustainable Production and Consumption, 2024)

Rice bran is a key structure affecting high nutrition and low toxicity of indica hybrid rice (Oryza sativa L.) - Yu Fan; Yujie Yuan; Zhiyou Gong; Yajun Wang; Xiufeng Mei; Fengjun Yan; Tao Wang; Fei Deng; Yong Chen; Xiaolong Lei; Jianfeng Hu; Youfeng Tao; et al. (Journal of Cereal Science, 2023)

Accumulated temperature and allocation of photo-thermal resources are key meteorological factors affecting rice cadmium content - Wei Zhou; Fengjun Yan; Yu Fan; Chi Zhang; Fan Yang; Qi Liu; Tao Wang; Bo Li; Yong Chen; Fei Deng; Jianfeng Hu; Xiaolong Lei; et al. (European Journal of Agronomy, 2023)

Improving yield and nitrogen use efficiency of hybrid indica rice through optimizing nitrogen application strategies in the rice season under different rotation patterns - YongJian Sun; Dan Lin; YuanYuan Sun; FengJun Yan; Peng Ma; ChangChun Guo; FeiJie Li; ZhiYuan Yang; FuXian Xu; Jun Ma (Paddy and Water Environment, 2023)

Differences in Rice Productivity and Growth Attributes Under Different Paddy-Upland Cropping Systems - Wei Zhou; Tao Wang; Yong Fu; Zhiping Yang; Qi Liu; Fengjun Yan; Yong Chen; Youfeng Tao; Wanjun Ren (International Journal of Plant Production, 2022)

Residual nitrogen from preceding garlic crops is important for double-cropped rice - Wei Zhou; Tao Wang; Yong Fu; Zhiping Yang; Qi Liu; Fengjun Yan; Yong Chen; Youfeng Tao; Nkrumah Malik; Wanjun Ren (Nutrient Cycling in Agroecosystems, 2020)

The effect of straw mulch on nitrogen, phosphorus and potassium uptake and use in hybrid rice - Fengjun Yan; Yongjian Sun; Xu Hui; Mingjin Jiang; Kaihong Xiang; Yunxia Wu; Qiao Zhang; Yuan Tang; Zhiyuan Yang; Yuanyuan Sun; Ma Jun (Paddy and Water Environment, 2019)

Effects of wheat straw mulch application and nitrogen management on rice root growth, dry matter accumulation and rice quality in soils of different fertility - Fengjun Yan; Yongjian Sun; Hui Xu; Yaozhu Yin; Haiyue Wang; Chunyu Wang; Changchun Guo; Zhiyuan Yang; Yuanyuan Sun; Jun Ma (Paddy and Water Environment, 2018)